Comparative Study of Image Quality and Radiation Dose between 120kvp Filtered Back Projection and 80kvp Iterative Reconstructed Computed Tomography Images - Joshi, Sweta; Paudel, Sharma; Suwal, Sundar; Shrestha, Shanta Lall; Lohani, Benu; Singh, Shashi Shekhar (Journal of Karnali Academy of Health Sciences, 2023)
Background: Iterative Reconstruction techniques have been shown to produce diagnostically acceptable images at low doses to the patient. This study aimed to compare the image quality and radiation dose between 120kVp Filtered Back Projection and 80kVp Iterative Reconstructed (SAFIRE) CT images. Methods: This cross-sectional study was performed on patients referred for CT Urography examinations for various clinical indications to the Department of Radiology and Imaging, Tribhuvan University Teaching Hospital. Data were collected for a period of four months (From August to November 2019) after approval from the Institutional Review Committee of the Institute of Medicine. Convenience sampling was employed and a total of 96 examinations were included. Among them 48 were male and 48 were female. Data were obtained from the 128-slice MDCT Siemens Somaton Definition AS+ CT scanner. Venous phase scans were obtained with Protocol A (120kVp and Filtered Back Projection) and non-contrast scans were obtained with Protocol B (80kVp and SAFIRE). The mAs (tube current-time product) was fixed at 200 for both protocols. Results: There was a 72.5% reduction in Size Specific Dose Estimate (SSDE) in Protocol B compared to Protocol A. However, there was a 13.17% increase in noise in Protocol B compared to Protocol A. Image quality evaluation showed a 98.95% acceptability for the low dose i.e. Protocol B images. Conclusion: CT using low kVp (80kVp) and low current (200mAs) along with an iterative reconstruction algorithm (SAFIRE) can provide diagnostically acceptable images at very low doses for examinations of the Urinary tract